A Contrastive Analysis of English Novel The Notebook and Its Chinese Translation from the Perspective of Rewriting Theory - Huang, Siyun (Advances in Social Sciences Research Journal, 2020)
The Notebook, American novelist Nicholas Sparks’ first romance novel, was published in 1996 and adapted into a movie in 2004 for 115 million box office worldwide. This study selects the original works and Chinese translation for contrastive research. Based on Andre Lefevere’s rewriting theory, this study makes an in-depth analysis of the difference of Ideology and Poetics between the two versions, and explores the reasons for favor from Chinese readers under the influence of ideology and poetics. This study comes to the following conclusions: in terms of ideology, the influence of social ideology on the translator and translator’s understanding of characters have led to language differences between two versions. From the perspective of Poetics, the terms of the original English text are relatively simple and easy to understand, while Chinese translators use a large number of allusions, folk adages and rhetorical devices to arouse interest. A contrastive analysis of two versions from the perspective of rewriting theory provides a completely new perspective for translation studies of novels. Translation studies are no longer confined to the linguistic level, but to the macro level such as culture and society.